Wisdom from laughter 500 jokes with life lessons - Oh, Teik Bin; Lee, Kiang Wui (Advantages Quest Publication, 2011)
Wisdom from Laughter is an interesting collection of 500 jokes which are bound to tickle your funny bone. Peppered with illustrations and cartoon drawings, Wisdom from Laughter contains a hearty blend of different jokes with a dash of spice. Each joke is unique and has been selected exclusively to teach perennial life lessons like compassion, kindness, common sense, or even morality through laughter. There is a point of reflection after that which will help you pause and reinforce the subtle nuances behind the joke and help you make wiser decisions. Laughter, they say, is the best medicine so whether you choose to read a joke a day or read it all at once, pick up the book, lower your blood pressure and laugh heartily.